2016
DOI: 10.1158/1940-6207.capr-15-0412
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Urinary PGE-M Are Found in Tobacco Users and Indicate a Poor Prognosis for Oral Squamous Cell Carcinoma Patients

Abstract: Cyclooxygenase-2 (COX-2)-derived prostaglandin E 2 (PGE 2 ) plays a role in the development and progression of epithelial malignancies. Measurements of urinary PGE-M, a stable metabolite of PGE 2 , reflect systemic PGE 2 levels. Here, we investigated whether urinary PGE-M levels were elevated in healthy tobacco users and in patients with oral squamous cell carcinoma (OSCC). Median urinary PGE-M levels were increased in healthy tobacco quid chewers [21.3 ng/mg creatinine (Cr); n ¼ 33; P ¼ 0.03] and smokers (32.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Bacteria are able to assimilate phosphate better than algae, especially at low concentrations 43 , and compete with algae for inorganic nutrients 44 . This increased pressure may stimulate PGs synthesis in diatoms as already shown in animals, where COX expression is stimulated in the presence of bacteria 45 and in humans where PGE 2 have been correlated to viral load and infection severity in influenza [46][47][48][49] . In line with this hypothesis, similar compounds, such as hydroxylated eicosapentaenoic acid 15-HEPE, were shown to be up-regulated and released from cells when the diatom S. marinoi was exposed to pathogenic bacteria 50 .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Bacteria are able to assimilate phosphate better than algae, especially at low concentrations 43 , and compete with algae for inorganic nutrients 44 . This increased pressure may stimulate PGs synthesis in diatoms as already shown in animals, where COX expression is stimulated in the presence of bacteria 45 and in humans where PGE 2 have been correlated to viral load and infection severity in influenza [46][47][48][49] . In line with this hypothesis, similar compounds, such as hydroxylated eicosapentaenoic acid 15-HEPE, were shown to be up-regulated and released from cells when the diatom S. marinoi was exposed to pathogenic bacteria 50 .…”
Section: Discussionmentioning
confidence: 67%
“…In line with this hypothesis, similar compounds, such as hydroxylated eicosapentaenoic acid 15-HEPE, were shown to be up-regulated and released from cells when the diatom S. marinoi was exposed to pathogenic bacteria 50 . PGE 2 is the most abundant prostanoid in the human body, but it is also very unstable since it is rapidly converted into PGE-M [46][47][48][49] that is considered to mirror the systemic levels of PGE 2 formation. In our study, PGE 2 was present at low levels in the medium during the exponential growth phase and was almost absent in the late stationary phase (from day 7) while PGE-M levels increased exponentially up to the senescent phase (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Reporting of clinical demographics was not consistent in each study. Of the 30 studies, only 10 fully reported all clinical demographics [28,30,34,35,38,41,43,47,49,51], 13 reported at least patient age, gender, and clinical stage [16,25,26,31,36,39,40,42,45,46,48,52,53]. Seven studies did not report differences in metabolite profile at different tumour stages [24,27,29,32,36,37,46].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…Out of 30 studies, only 12 declared evidence of data preprocessing [25,29,33,34,36,37,40,41,43,45,48,49]. Levels one, two, and three metabolite identification were reported in nine [25,27,30,32,36,39,40,46,52], 15 [16,24,26,29,33,34,37,42,43,45,47,49,51,56,58], and six [28,31,35,38,41,48] studies, respectively. Only two of the 30 studies reported all of the statistical aspects suggested by the CAWG-MSI guidelines [59].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…Previous reports have suggested a correlation between expression of COX‐2, occurrence of oral cancer, and a worse prognosis (Wang et al., ). COX‐2 levels are induced by tobacco carcinogens (Kekatpure et al., ) and are observed at high levels in leukoplakias and primary and metastatic squamous carcinomas of the head and neck (Javed & Warnakulasuriya, ). Use of NSAIDs has been associated with a reduced risk of HNSCC in some epidemiologic studies (Ahmadi et al., ; Tang et al., ).…”
Section: Non‐steroidal Anti‐inflammatory Drugs (Nsaids)mentioning
confidence: 99%